2011
DOI: 10.1016/j.ijgo.2010.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Impact of seroconversion and antichlamydial treatment on the rate of pre‐eclampsia among Egyptian primigravidae

Abstract: The present results indirectly support the hypothesis that infectious agents (in particular C. pneumoniae) have a role in the development of pre-eclampsia. The findings also indicate that antichlamydial treatment might help to reduce the incidence of pre-eclampsia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…In the present study the prevalence of C.pneumoniae IgG seropositivity among primigravidae estimated at 14-20 weeks of gestation was 32.4% (108/330), which was similar to other reports of Dadelszen V et al (39%), Karinen et al (28.8%), and El-Shourbagy (37%); whereas higher seroprevalence was reported by Heine (54%), Awoeleke (66%) and Goulis et al (77%). [12][13][14][15][16][17][18] The present study as well as that of El-Shourbagy et al found no association of C. pneumoniae IgG seropositivity with age or BMI, even though two recent studies have shown that C.pneumoniae is capable of infecting preadipocytes and adipocytes and there could be a possible association between seroprevalence of C.pneumoniae and high BMI. 18,25,26 In For studying the association of seropositivity with preeclampsia we compared seropositive untreated and seronegative groups so that the data is not skewed due to effect of treatment; the incidence of PE being 13% (7/54) and 4% (9/222) respectively, indicating higher incidence of PE in seropositive untreated group compared to seronegative group (p=0.023).…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…In the present study the prevalence of C.pneumoniae IgG seropositivity among primigravidae estimated at 14-20 weeks of gestation was 32.4% (108/330), which was similar to other reports of Dadelszen V et al (39%), Karinen et al (28.8%), and El-Shourbagy (37%); whereas higher seroprevalence was reported by Heine (54%), Awoeleke (66%) and Goulis et al (77%). [12][13][14][15][16][17][18] The present study as well as that of El-Shourbagy et al found no association of C. pneumoniae IgG seropositivity with age or BMI, even though two recent studies have shown that C.pneumoniae is capable of infecting preadipocytes and adipocytes and there could be a possible association between seroprevalence of C.pneumoniae and high BMI. 18,25,26 In For studying the association of seropositivity with preeclampsia we compared seropositive untreated and seronegative groups so that the data is not skewed due to effect of treatment; the incidence of PE being 13% (7/54) and 4% (9/222) respectively, indicating higher incidence of PE in seropositive untreated group compared to seronegative group (p=0.023).…”
Section: Discussionsupporting
confidence: 56%
“…[12][13][14] Association between C.pneumoniae seroprevalence and preeclampsia has been proven by many studies. [13][14][15][16][17][18][19] El-Shourbagy MA et al, in one study showed a reduced incidence of preeclampsia after giving treatment to C.pneumoniae seropositive women. 17 However, other studies showed conflicting results.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Significantly greater numbers with PE, and reversion under antichlamydial treatment [313] Much greater incidence (P<0.006) [ Anti-CagA antibodies crossreact with trophoblasts and could inhibit placentation [322] 2.8x greater seropositivity in PE group [323] OR=2.86 for seropositivity in PE, correlated with high malondialdehyde levels [324] Wide-ranging review of many studies showing PE more prevalent after Hp infection [325] Seropositivity PE:control = 84%:32% (P<0.001) [326] OR for seropositivity 1.83 (P<0.001) [327] Seropositivity PE:control 86%:43% (P<0.001) [328] Massive increase in seropositivity in women with PE [329] Seroprevalence (57%) > controls (33.%) (P<.001). Seropositivity for CagA-positive strains 45.2% in preeclamptic women vs 13.7% in controls (P<.001).…”
Section: Chlamydia Pneumoniaementioning
confidence: 94%
“…2;3 There are several hypothesized causes of the exaggerated inflammatory response to pregnancy among preeclamptic women, including increased trophoblast debris released by a dysfunctional placenta, 4 placental ischemia, 5 or bacterial and viral infections, known to elicit an overall upregulation of immune mediators and oxidative stress. 1;2;617 As the causes of inflammation seen in preeclampsia are not clear, we performed a nested case-control study examining the relationships between primary infection with Chlamydia trachomatis, Chlamydia pneumoniae , cytomegalovirus (CMV), herpes simplex virus (HSV), and preeclampsia, within the Collaborative Perinatal Project (CPP) of 55,908 pregnancies.…”
Section: Introductionmentioning
confidence: 99%